Advertising engagement: conceptualization, scale development and validation - Dr. Haluk AKARSU,Prof. Dr. Necip Serdar SEVER (Fonseca, Journal of Communication, 2023)
Even though there is wide use of the advertising engagement concept in the advertising sector, only a limited number of studies have focused on the concept and the measurement of the construct. Furthermore, there is a lack of consensus regarding the conceptualization of engagement in the marketing and advertising literature. In this study, we conceptualize advertising engagement and develop a 24-item scale called ‘Engagement Towards Advertisement’ (EA), which includes two factors: behavioral intention and mental processing.